Indicative value of benthic foraminifera for biomonitoring: Assignment to ecological groups of sensitivity to total organic carbon of species from European intertidal areas and transitional waters. (March 2021) - Bouchet, Vincent M.P.; Frontalini, Fabrizio; Francescangeli, Fabio; Sauriau, Pierre-Guy; Geslin, Emmanuelle; Martins, Maria Virginia Alves; Almogi-Labin, Ahuva; Avnaim-Katav, Simona; Di Bella, Letizia; Cearreta, Alejandro; Coccioni, Rodolfo; Costelloe, Ashleigh; et al.
Abstract: This work contributes to the ongoing work aiming at confirming benthic foraminifera as a biological quality element. In this study, benthic foraminifera from intertidal and transitional waters from the English Channel/European Atlantic coast and the Mediterranean Sea were assigned to five ecological groups using the weighted-averaging optimum with respect to TOC of each species. It was however not possible to assign typical salt marsh species due to the presence of labile and refractory organic matter that hampers TOC characterization. Tests of this study species' lists with Foram-AMBI on two independent datasets showed a significant correlation between Foram-AMBI and TOC, confirming the strong relation between foraminifera and TOC. For one of the validation datasets, associated macrofaunal data were available and a significant correlation was found between the foraminiferal Foram-AMBI and the macrofaunal AMBI. The here proposed lists should be further tested with sensitivity-based indices in different European regional settings. Highlights: Benthic foraminifera from transitional waters were assigned to ecological groups of sensitivity to total organic carbon. Typical salt marsh species could not be assigned. Indicative value of each species with respect to TOC was estimated with the weighted-averaging method. Tests of the species' lists on two independent data sets with Foram-AMBI showed a reliable assessment of EcoQS. Efforts are needed to homogenize foraminiferal taxonomy, including a combination of molecular and morphological techniques.